Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 9 - Cumulative Review: 39


$ f^{-1}(x)=x-3$

Work Step by Step

We are given the function, $f(x)=x+3$. First, we must replace $f(x)$ with y. $y=x+3$ Next, interchange x and y. $x=y+3$ Next, solve for y by subtracting 3 from both sides. $y=x-3$ Finally, replace y with $f^{-1}(x)$. $ f^{-1}(x)=x-3$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.